Wavelength modulation spectroscopy for measurements of gas parameters in combustion field - 屈东胜 洪延姬 王广宇 潘虎 (Chinese physics B, 2017)
A novel wavelength modulation spectroscopy sensor for studying gas properties near 1.4 μm is developed, validated and used in a direct-connect supersonic combustion test facility. In this sensor there are two H2O transitions near 7185.60 cm^-1 and 7454.45 cm^-1 that are used to enable the measurements along the line-of-sight. According to an iterative algorithm, the gas pressure, temperature and species mole fraction can be measured simultaneously. The new sensor is used in the isolator and extender of the supersonic combustion test facility. In the isolator, the sensor resolves the transient and measured pressure, temperature and H2O mole fraction with accuracies of 2.5%, 8.2%, and 7.2%, respectively. Due to the non-uniform characteristic in the extender, the measured results cannot precisely characterize gas properties, but they can qualitatively describe the distinctions of different zones or the changes or fluctuations of the gas parameters.